The Marseilles working-class movement, 1936-1938 - Levy, D; Levy, D. A. L. (1983)
﻿ The purpose of this thesis is threefold: firstly, to serve as a contribution to the history of the Marseilles working class; secondly to illustrate the impact of the Popular Front at local level; and thirdly, to act as a case study of working-class mobilisation. In the first section of the thesis the Marseilles working class is briefly described. It was highly heterogeneous, being made up of various racially, occupationally, and spatially-defined communities. The divisions between these communities were to some extent neutralised by a strong sense of the local community of Marseilles. Marseilles' claim to special status within the nation was, however, increasingly coming under challenge. Prior to the Popular Front the most successful political organisations on the Left in Marseilles integrated themselves into the rich community life of the town by playing down ideological issues and by practising the politics of locally-based clientelism rather than those of class. The movement for the Popular Front encouraged a new mood of militancy within the Marseilles working class which both contributed to, and was itself encouraged by, the growth of Communist influence within the Popular Front alliance. At different moments the strikes of the period facilitated or prejudiced the unity of the working class and its integration into the nation. Initially (1934-1937), the strikes which were undertaken advanced the interests of workers against those of employers whilst increasing working-class unity and support for the Popular Front. At the same time the election of a Popular Front Government and its success in resolving strikes to the satisfaction of workers aided the integration of the working class into a new, enlarged, national political consensus. The fragility of this consensus was, however, later revealed (1938-1939), as the Government called for sacrifices in the workplace and the Communists called fcr the launching of an unpopular war against fascism.